2021
DOI: 10.3390/app11219969
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Working Conditions of Mining Workers by Reducing Nitrogen Oxide Emissions during Blasting Operations

Abstract: The article presents comparison of the values of maximum permissible concentrations, revealed during the analysis of the national standards of Russia and Australia in the field of regulation of nitrogen oxides. The impact of poisoning of the workers of the quarry with nitrogen oxides after blasting operations are presented. A detailed review of studies of methods for reducing nitrogen oxide emissions is given. The way of decreasing emission of nitrogen oxides using highly active catalysts as a part of the prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…qualitatively and quantitatively evaluated the harmful gas composition in large-scale blasting of quarries. Rudakov Marat [ 9 ] proposed the way of decreasing emission of nitrogen oxides using highly active catalysts as a part of the profiled tamping. And the results obtained showed that zinc carbonate (ZnCO 3 ) is the most effective.…”
Section: Introductionmentioning
confidence: 99%
“…qualitatively and quantitatively evaluated the harmful gas composition in large-scale blasting of quarries. Rudakov Marat [ 9 ] proposed the way of decreasing emission of nitrogen oxides using highly active catalysts as a part of the profiled tamping. And the results obtained showed that zinc carbonate (ZnCO 3 ) is the most effective.…”
Section: Introductionmentioning
confidence: 99%
“…Harris analyzed the CO generated by mine-blasting operations and showed that applying negative pressure to the borehole was the most effective method of removing CO from the surface and minimizing its accumulation and migration [26]. Rudakov et al improved the filling of explosives and provided a method to reduce nitrogen oxide emissions by using highly active catalysts as a part of the molding and tamping process [27]. The results showed that using zinc carbonate (ZnCO 3 ) as a filler reduced nitrogen oxide emissions by 40% without the addition of catalysts.…”
Section: Introductionmentioning
confidence: 99%